RANCANG BANGUN KONTROL MOTOR AC SATU FASA MENGGUNAKAN VISUAL STUDIO BERBASIS ARDUINO - Alpian Martalata; Rudy Kurniawan; Tri Hendrawan Budianto (ELECTRON : Jurnal Ilmiah Teknik Elektro, 2018)
The control system of single phase induction motor control the most commonly used is the control system using tangang starter. Ie controlling the operator control must interact directly with the motor control equipment in terms of start, stop and control the speed of motor rotation. To facilitate the required motor control a motor control system which is programmed visually so the operator will be easier and safer to control the single-phase induction motor using a computer. Motor control with visual control systems programmed to do by utilizing Arduino microcontroller as controller of motor control equipment, as well as visual studio used to interface with the operator and motors.